2003
DOI: 10.2527/2003.8161434x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of acid-base balance in Bos indicus steers subjected to transportation of long duration1

Abstract: There is a lack of information pertaining to the effects of transport stress on the acid-base physiology of ruminants. The effect of transportation and/or feed and water deprivation on acid-base balance was studied using 19 2-yr-old Bos indicus steers. The steers were allocated to one of three groups: 1) control, offered ad libitum access to feed and water (n = 8); 2) water and feed deprived, offered no feed or water for 60 h (n = 6); and 3) transported, offered no feed or water for 12 h, and then transported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 29 publications
7
39
1
4
Order By: Relevance
“…This observation is in agreement with previous reports (Parker et al, 2003;Earley et al, 2006a;Earley and O'Riordan, 2006b). However, another study reported a decrease in plasma protein after a 9-h transportation event (Buckham Sporer et al, 2008).…”
Section: Plasma Proteinsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is in agreement with previous reports (Parker et al, 2003;Earley et al, 2006a;Earley and O'Riordan, 2006b). However, another study reported a decrease in plasma protein after a 9-h transportation event (Buckham Sporer et al, 2008).…”
Section: Plasma Proteinsupporting
confidence: 94%
“…However, in a study investigating the partial pressure of carbon dioxide after transportation, no difference was reported for transported steers compared to control animals (Parker et al, 2003). Total carbon Figure 6.…”
Section: Total Carbon Dioxidementioning
confidence: 95%
“…The availability of Na in the rumen during FWD may need to be reassessed. It may also explain the maintenance of acid -base balance observed by Parker et al 70 during 48 h FWD plus transport in steers. When animals come under the restrictions of FWD, rumination is greatly reduced and practically ceases within 24 h 71 .…”
Section: Homeostasismentioning
confidence: 58%
“…Changes in mineral metabolism triggered off by alterations in the original hormonal status, as a result of environmental stress factors brought about during animal transportation involve chiefly calcium, magnesium, sodium, potassium and chloride (Klaus-Dietrich, 1985, Parker et al, 2003. Stress causes cell stimulation, resulting in an aggressive potential change of cell from rest potential to action potential (Klaus-Dietrich, 1985).…”
Section: Effects Of Transportation Stress On Biochemical Parametersmentioning
confidence: 99%
“…A rise in calcium ion concentration in stressed animals is also manifested by increase in muscle activeties (Klaus-Dietrich, 1985). Decrease in potassium concentration observed in animals exposed to stress may be due to the fact that stress induced activation of the hypothalamic-pituitary-adrenal axis and stimulated the secretion of cortisol, resulting in excretion of K + (Parker et al, 2003). The changes in the ion milieu give rise to nervous hypersensitive reactions in animals (White et al, 1991;Skull and Rodiek, 2000).…”
Section: Effects Of Transportation Stress On Biochemical Parametersmentioning
confidence: 99%